2006
DOI: 10.1007/s00428-006-0196-3
|View full text |Cite
|
Sign up to set email alerts
|

Cystic cholangiomas after transplantation of pancreatic islets into the livers of diabetic rats

Abstract: Islet transplantation is increasingly used as a therapy for human type 1 diabetes mellitus. In our study, we investigated the effect of the transplantation of a low number (n = 350) of pancreatic islets into the right liver part on the neighboring portal bile ducts. Male streptozotocin- diabetic Lewis or autoimmune-diabetic BB/Pfd rats (n = 1065) were subdivided into 11 experimental groups. A few days after low-number islet transplantation, cholangiocytes adjacent to the grafts showed an increase in proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Hepatic steatosis has been reported in a subset of allotransplanted subjects, but clinical sequelae have not yet been noted [28]. Although liver neoplasms after ITx have been observed in rodents [29,30], no human cases have been reported. Insulin resistance estimated from the HOMA-IR index was increased in both the Px and Px + ITx groups, unlike in the normal control group.…”
Section: Discussionmentioning
confidence: 95%
“…Hepatic steatosis has been reported in a subset of allotransplanted subjects, but clinical sequelae have not yet been noted [28]. Although liver neoplasms after ITx have been observed in rodents [29,30], no human cases have been reported. Insulin resistance estimated from the HOMA-IR index was increased in both the Px and Px + ITx groups, unlike in the normal control group.…”
Section: Discussionmentioning
confidence: 95%
“…We have also validated this technique for use as a means of reproducible, quantitative, histological, and morphometrical analysis of islet graft survival [14][15][16]. Using the selective intraportal transplantation model, we compared the number of histologically visualized, intraportally transplanted islets with that of similarly transplanted dextran beads.…”
Section: Introductionmentioning
confidence: 99%
“…12,15,27 Sometimes, we observed the development of morphologically similar cystic cholangiomas without discovering any preceding oval cell proliferation and CF. Evert et al 28 have demonstrated that this pathogenesis is the rule rather than the exception after transplantation of pancreatic islands into the livers of diabetic rats. The cholangiomas developing under these conditions emerged from cholangiocytes adjacent to the transplanted islands and turned out to be benign end-stage lesions like those originating from mucus CF in other models.…”
mentioning
confidence: 99%
“…The progression from peri-insular ductules to cystic cholangiomas after islet cell transplantation in diabetic rats was accompanied by a translocation of the insulin receptor from the cell membrane into the cytoplasm and an increase in expression of insulin-related signaling proteins (insulin-receptor-substrate-1, Raf-1, Mek-1) in the cholangiolar cells involved. 28…”
mentioning
confidence: 99%